2012
DOI: 10.4269/ajtmh.2012.11-0569
|View full text |Cite
|
Sign up to set email alerts
|

Climate Predictors of the Spatial Distribution of Human Plague Cases in the West Nile Region of Uganda

Abstract: Abstract. East Africa has been identified as a region where vector-borne and zoonotic diseases are most likely to emerge or re-emerge and where morbidity and mortality from these diseases is significant. Understanding when and where humans are most likely to be exposed to vector-borne and zoonotic disease agents in this region can aid in targeting limited prevention and control resources. Often, spatial and temporal distributions of vectors and vector-borne disease agents are predictable based on climatic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
(95 reference statements)
2
25
0
Order By: Relevance
“…For example Neerinckx et al (2008Neerinckx et al ( , 2010 reported a positive correlation of high plague frequency at an elevation above 1,500m in West Usambara Mountains. Similar results have been reported by MacMillan et al (2012) who indicated a high correlation between plague hosts and elevation above 1,300m in a plague focus in Uganda. Also, elevation has been reported to influence plague host occurrence in Turkey (Yigit et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…For example Neerinckx et al (2008Neerinckx et al ( , 2010 reported a positive correlation of high plague frequency at an elevation above 1,500m in West Usambara Mountains. Similar results have been reported by MacMillan et al (2012) who indicated a high correlation between plague hosts and elevation above 1,300m in a plague focus in Uganda. Also, elevation has been reported to influence plague host occurrence in Turkey (Yigit et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, covariates included in these models suggested that localities that are generally wetter, but with discontinuous rainfall, pose an increased risk for plague compared with drier areas. 11,12,14 Although existing spatial models performed well in broadly defining the plague focus, there were many villages within the focus where human plague cases had not been reported by clinics during approximately a decade of surveillance. Such an observation raised the question of whether these disparities in case counts among villages within the risk area were attributable to differences in access to care, care-seeking behavior or knowledge of plague, agricultural or food storage practices, rodent and vector control strategies, or fine-scale ecologic differences (e.g., differences in host and flea community structure).…”
Section: Introductionmentioning
confidence: 99%
“…10 To aid in better targeting plague prevention resources, recent research efforts in Uganda have sought to define when and where humans are most at risk for plague in the far eastern edge of this plague focus. [11][12][13][14] During August 1999-July 2011, a total of 2,409 suspect plague cases were reported from the West Nile Region of Uganda; most cases occurred during September-December, a time period that corresponds with the primary rainy season. 13 Modeling of inter-annual variation showed that annual plague case counts were negatively associated with dry season rainfall (December-February) and positively associated with rainfall immediately preceding the plague season.…”
Section: Introductionmentioning
confidence: 99%
“…However, in other tropical and sub-tropical regions plague generally occurs during the rainy season or shows no clear seasonal pattern [44], [45]. In addition, previous research in the West Nile region of Uganda established a positive link between rainfall in February, October, and November (but a negative association with June rainfall) and the spatial risk of plague [40].…”
Section: Discussionmentioning
confidence: 99%